A comparison among citation-based journal indicators and their relative changes with time. Issue 1 (February 2020) - Liu, Xuan Zhen; Fang, Hui
Highlights: JIF2 increased faster than JIF5 overall. The control of JCR over journal self-citation is effective, though not perfect. Differences in journal rankings based on different indexes may be large. The correlation between JIF5 and the article influence score is strong. Journals in a subject category may have considerably different citation patterns. Abstract: This study compares the two-year impact factor (JIF2), JIF2 without journal self-citation (JIF2_noJSC), five-year impact factor (JIF5), eigenfactor score and article influence score (AIS) and investigates their relative changes with time. JIF2 increased faster than JIF5 overall. The relative change between JIF2 and JIF_noJSC shows that the control of JCR over journal self-citation is effective to some extent. JIF5 is more discriminative than JIF2. The correlation between JIF5 and AIS is stronger than that between JIF5 and the eigenfactor score. The relative change in journal rank according to different indicators varies with the ratio of the indicators and can be up to 60 % of the number of journals in a subject category. There is subject category discrepancy in the average AIS and its change over time. Through the screening of journals according to variations in the ratio of JIF2 to JIF5 for journals in individual subject categories, we found that journals in the same subject categories can have considerably different citation patterns. To provide a fair comparison of journals in individual subject categories, we argue that it is better to replace JIF2 with the ready-made JIF5 when ranking journals.